Crosstalk between Long-Term Sublethal Oxidative Stress and Detrimental Inflammation as Potential Drivers for Age-Related Retinal Degeneration - Lara Macchioni; Davide Chiasserini; Letizia Mezzasoma; Magdalena Davidescu; Pier Luigi Orvietani; Katia Fettucciari; Leonardo Salviati; Barbara Cellini; Ilaria Bellezza (MDPI AG, 2020)
Age-related retinal degenerations, including age-related macular degeneration (AMD), are caused by the loss of retinal pigmented epithelial (RPE) cells and photoreceptors. The pathogenesis of AMD, deeply linked to the aging process, also involves oxidative stress and inflammatory responses. However, the molecular mechanisms contributing to the shift from healthy aging to AMD are still poorly understood. Since RPE cells in the retina are chronically exposed to a pro-oxidant microenvironment throughout life, we simulated in vivo conditions by growing ARPE-19 cells in the presence of 10 μM H2O2 for several passages. This long-term oxidative insult induced senescence in ARPE-19 cells without affecting cell proliferation. Global proteomic analysis revealed a dysregulated expression in proteins involved in antioxidant response, mitochondrial homeostasis, and extracellular matrix organization. The analyses of mitochondrial functionality showed increased mitochondrial biogenesis and ATP generation and improved response to oxidative stress. The latter, however, was linked to nuclear factor-κB (NF-κB) rather than nuclear factor erythroid 2-related factor 2 (Nrf2) activation. NF-κB hyperactivation also resulted in increased pro-inflammatory cytokines expression and inflammasome activation. Moreover, in response to additional pro-inflammatory insults, senescent ARPE-19 cells underwent an exaggerated inflammatory reaction. Our results indicate senescence as an important link between chronic oxidative insult and detrimental chronic inflammation, with possible future repercussions for therapeutic interventions.